Pathogenic mechanisms involved in the hematological alterations of arenavirus-induced hemorrhagic fevers - Schattner, Mirta (2013)
Viral hemorrhagic fevers (VHFs) caused by arenaviruses are acute diseases characterized by fever, headache, general malaise, impaired cellular immunity, eventual neurologic involvement, and hemostatic alterations that may ultimately lead to shock and death. The causes of the bleeding are still poorly understood. However, it is generally accepted that these causes are associated to some degree with impaired hemostasis, endothelial cell dysfunction and low platelet counts or function. In this article, we present the current knowledge about the hematological alterations present in VHF induced by arenaviruses, including new aspects on the underlying pathogenic mechanisms.